2006
DOI: 10.1007/s00068-006-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Insertion of Optional Vena Cava Filters in High-Risk Trauma Patients

Abstract: Ab stractBackground: Vena cava interruption is a form of pulmonary embolism prophylaxis that is being used in high-risk patients who do not tolerate pharmacologic prophylaxis. Retrievable prophylactic vena cava filters (VCFs) are of particular interest for severely injured patients where the necessity for VCF is often only temporary. Methods: In a single-institution case series of consecutive patients who received prophylactic VCFs after polytrauma, between 04/1998 and 07/2004, the demographic data, injury pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Prophylactic insertion of optional VCF in high-risk patients has shown to provide effective protection from potentially fatal PE with low insertion -and retrieval related morbidity [24][25][26][27][28]. With the safety of LDUH and LMWH not being established yet, early placement of VCF may be an alternative method of PE prophylaxis in TBI patients with severe additional injuries at risk for potential intracranial bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic insertion of optional VCF in high-risk patients has shown to provide effective protection from potentially fatal PE with low insertion -and retrieval related morbidity [24][25][26][27][28]. With the safety of LDUH and LMWH not being established yet, early placement of VCF may be an alternative method of PE prophylaxis in TBI patients with severe additional injuries at risk for potential intracranial bleeding complications.…”
Section: Discussionmentioning
confidence: 99%
“…Retrieval rate reached 52% with a mean indwelling time of 71 days. In a previous study, we reported our experience with prophylactic insertion of optional VCF in multiple injured patients with a median ISS of 38 [26]. From a total of 95 VCF placed before August 2004 68% were retrieved after 13 days with a maximal indwelling time of 25 days.…”
Section: Discussionmentioning
confidence: 99%